Attributes of excellent surgical trainers: An analysis of outstanding trainers. (April 2018) - Sutton, P.A.; Beamish, A.J.; Rashid, S.; Elsey, E.; Mohan, H.M.; O'Regan, D.
Abstract: Excellent surgical trainers play a key role in teaching, mentoring and inspiring the next generation of trainee surgeons. Although there are differences in approach, personality and technique among trainers, common themes exist for those that truly shine as examples of good training. The good surgical trainer has long been the "unsung hero" of patient safety, inspiring and imparting wisdom and skill in trainee surgeons, and instilling a sense of confidence and compassion. In order to recognise exceptional trainers, the Association of Surgeons in Training (ASiT) introduced the Silver Scalpel Award in 2000. The award acknowledges talented trainers who go the "extra mile" for their trainees, and the selection process includes both written nominations and structured interviews with the nominees. We wished to identify what makes the best trainers excellent, to see if these attributes could be used to develop recommendations on how to train and how to support trainers. Here we present an outline of key attributes of an excellent surgical trainer, based on qualitative synthesis of the interview sheets from Silver Scalpel interviews. These results clearly highlight that good trainers are first and foremost good doctors, and that good training goes hand-in-hand with excellent patient care. This symbiotic relationship between training and patient outcomes should be acknowledged, and trainers should be supported by their employers to empower them to carry out their dual roles of training and patient care to the best of their ability. Trainers are key role models to inspire the next generation of surgeons and exceptional trainers should be celebrated.